2019
DOI: 10.3390/cryst9040183
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Thermal Formation of Uniform Lying Helix Alignment in a Cholesteric Liquid Crystal Cell

Abstract: We demonstrated previously that the temperature of a sandwich-type liquid crystal cell with unignorable electrode resistivity could be electrically increased as a result of dielectric heating. In this study, we take advantage of such an electro-thermal effect and report on a unique electric-field approach to the formation of uniform lying helix (ULH) texture in a cholesteric liquid crystal (CLC) cell. The technique entails a hybrid voltage pulse at frequencies f1 and, subsequently, f2, which are higher and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…[80,81] Indirect heating by applying an electric field can also be used to generate photonic bandgap tuning in CLC systems in a fashion similar to that described earlier. [76,[82][83][84][85] Electrothermal color tuning is possible by applying an electric field between two conductive substrates [76,84,86] or using only one conductive substrate with a specifically designed interdigitated electrode pattern [85] Figure 5. Demonstration of a TR-RC CLC system (LC host: BL006, chiral dopant: ZLI-811, i.e., S811) based on the chiral dopant solubility.…”
Section: Tr-rc Tendencymentioning
confidence: 99%
See 1 more Smart Citation
“…[80,81] Indirect heating by applying an electric field can also be used to generate photonic bandgap tuning in CLC systems in a fashion similar to that described earlier. [76,[82][83][84][85] Electrothermal color tuning is possible by applying an electric field between two conductive substrates [76,84,86] or using only one conductive substrate with a specifically designed interdigitated electrode pattern [85] Figure 5. Demonstration of a TR-RC CLC system (LC host: BL006, chiral dopant: ZLI-811, i.e., S811) based on the chiral dopant solubility.…”
Section: Tr-rc Tendencymentioning
confidence: 99%
“…Indirect heating by applying an electric field can also be used to generate photonic bandgap tuning in CLC systems in a fashion similar to that described earlier. [ 76,82–85 ] Electrothermal color tuning is possible by applying an electric field between two conductive substrates [ 76,84,86 ] or using only one conductive substrate with a specifically designed interdigitated electrode pattern [ 85 ] that generates an in‐plane alternating current (AC) electric field. To give an example of electrothermally driven bandgap shifting, a CLC system consisting of a nematic LC mixture MLC‐2138 and a chiral dopant S811 was used to fill a cell equipped with an interdigitated electrode pattern on top of a glass substrate.…”
Section: Temperature‐responsive Clcs In Different Configurationsmentioning
confidence: 99%
“…Besides, experiments using cells with various sets of cell parameters have also been carried out in our recent works. [26][27][28] It is concluded that the cell gap, the electrode area and the intrinsic dielectric anisotropy in LC used are responsible for the measured dielectric spectrum, thereby determining the profile of the pseudo-dielectric relaxation and the strength of the dielectric heating effect. For example, according to Eqs.…”
Section: Electro-thermal Tunability Of C and Reflective Colorsmentioning
confidence: 99%
“…The uniformity of ULH formed with this electric field approach has been improved by mechanically shearing the cell substrates simultaneously [10,11] or by modifying the surface alignment conditions with alternate stacking of planar and homeotropic alignment [12], or with helical-pitch-matched cholesteric alignment layer [13]. Other electric field approaches-including those based on voltage-induced electrohydrodynamic instability [14,15], flexoelectric effect [16], textural transition [17], electro-thermal effect [18], and adoption of tri-electrode configurations [19,20]-have been successively proposed for generating ULH alignment in a planar-aligned cell. Nevertheless, most ULH textures as prepared by the above-mentioned voltage pretreatments would be irreversibly destroyed or even transferred back to the most stable Grandjean planar texture after the CLC helix is partially or completely unwound by external voltages or the phase transition often occurs unwantedly by thermal variation; hence, making them incompatible for utilization of the flexoelectric or dielectric switching in extensive electro-optic applications.…”
Section: Introductionmentioning
confidence: 99%